Novel approaches to the treatment of bacterial biofilm infections. (2nd February 2017) - Hughes, Gareth; Webber, Mark A
Abstract : Bacterial infection remains a major challenge to healthcare and is responsible for significant morbidity and mortality. This situation is becoming complicated by an increasingly ageing and susceptible population and large numbers of bacterial isolates, which have developed resistance to antibiotics. Bacteria that form biofilms and colonize or infect medical devices or wounds are particularly hard to treat as biofilms are inherently highly antibiotic resistant. Most infections have a component where bacteria exist as a biofilm and as a result, prevention or treatment of biofilm‐associated infections is highly important. A number of novel strategies to kill biofilms have been in development; these include the use of weak organic acids, photo irradiation and the application of bacteriophage. All have promise and are able to effectively kill biofilms in model systems, but for each there are still unanswered questions. This review summarizes the main features of biofilm infections, each of these novel approaches and the evidence that is still lacking before these potential treatments can be incorporated into clinical usage. Linked Articles: This article is part of a themed section on Drug Metabolism and Antibiotic Resistance in Micro‐organisms. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.14/issuetoc